2022
DOI: 10.3390/diseases10040087
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Viral Infections in Gastroenterology

Abstract: Enteric viruses are commonly found obligate parasites in the gastrointestinal (GI) tract. These viruses usually follow a fecal-oral route of transmission and are characterized by their extraordinary stability as well as resistance in high-stress environments. Most of them cause similar symptoms including vomiting, diarrhea, and abdominal pain. In order to come in contract with mucosal surfaces, these viruses need to pass the three main lines of defense: mucus layer, innate immune defenses, and adaptive immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 110 publications
0
1
0
Order By: Relevance
“…Other studies found that the inhalation of LPS into the lungs of mice could increase the number of bacteria in the intestines, indicating that pneumonia has the capacity to affect intestinal homeostasis and induce intestinal injury [61]. Recent studies have found that SARS‐CoV‐2 causes diarrhea in patients by impacting gut microbiome, such as the phylum Firmicutes [62]. Furthermore, disruption of the lung microbiome may affect the homeostasis of the gut microbiome.…”
Section: The Microbiome In Lung Cancer Patientsmentioning
confidence: 99%
“…Other studies found that the inhalation of LPS into the lungs of mice could increase the number of bacteria in the intestines, indicating that pneumonia has the capacity to affect intestinal homeostasis and induce intestinal injury [61]. Recent studies have found that SARS‐CoV‐2 causes diarrhea in patients by impacting gut microbiome, such as the phylum Firmicutes [62]. Furthermore, disruption of the lung microbiome may affect the homeostasis of the gut microbiome.…”
Section: The Microbiome In Lung Cancer Patientsmentioning
confidence: 99%